2020
DOI: 10.3390/nu12092680
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Community-Based Interventions Programs in Childhood Obesity Prevention in a Spanish Population According to Different Socioeconomic School Settings

Abstract: Overweight and obesity amongst childhood are currently global health issues. However, this is the best stage of life to prevent diseases and to promote healthy habits. In our study, we evaluate the effectiveness of the THAO Salud Infantil, a community-based intervention program, by means of a cross-sectional study carried out from 2009 to 2019 surveying children aged 3 to 12 years old (n = 27,686). During the study timeframe, overweight and obesity prevalence, according to both the International Obesity Task F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Compared to other EPODE evaluations, our results were surprising. No other EPODE evaluations compared overweight prevalence in low SES and middle/high SES areas, however, a Spanish evaluation showed that overweight/obesity prevalence was higher among public school students, which are generally from lower SES families, than among charter and private schools, which are generally populated by higher SES students [ 19 ]. Other EPODE adaptation evaluation studies have controlled for maternal education [ 18 ], or a SES measure similar to ours [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other EPODE evaluations, our results were surprising. No other EPODE evaluations compared overweight prevalence in low SES and middle/high SES areas, however, a Spanish evaluation showed that overweight/obesity prevalence was higher among public school students, which are generally from lower SES families, than among charter and private schools, which are generally populated by higher SES students [ 19 ]. Other EPODE adaptation evaluation studies have controlled for maternal education [ 18 ], or a SES measure similar to ours [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth study is another evaluation of the Spanish EPODE adaptation and surveyed children living in intervention areas between 2009 and 2019. During this period of time, overweight and obesity prevalence decreased, however, the systematic effectiveness of the program is difficult to conclude as there was no comparison with a control group [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, the ultimate goal of home‐based interventions (Pamungkas & Chamroonsawasdi, 2019) and population‐wide policies (Keya et al, 2019) should be lifestyle modification, which is likely to have long‐term positive effects upon child development and overall public health (Hsiang et al, 2020; Salam et al, 2020). Taken together, because parental behaviors, family patterns, household conditions, and community factors shape child developmental and body weight trajectories, intervention programs, and public policies should include nutritional and physical activity education for parents (Chai et al, 2019; Dev et al, 2013; C. Li et al, 2020), make available healthy food choices at reasonable prices in local stores (Dolati et al, 2020), as well as provide financial investment into the physical and social infrastructures of the disadvantaged communities (e.g., creating neighborhood facilities for recreation; Puga et al, 2020).…”
Section: Discussionmentioning
confidence: 99%